2021
DOI: 10.1371/journal.pntd.0009331
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of conventional microbial culture for the Naja atra bite wound, and the comparison between culture-based 16S Sanger sequencing and 16S metagenomics of the snake oropharyngeal bacterial microbiota

Abstract: Naja atra is a major venomous snake found in Taiwan. The bite of this snake causes extensive wound necrosis or necrotizing soft tissue infection. Conventional microbial culture-based techniques may fail to identify potential human pathogens and render antibiotics ineffective in the management of wound infection. Therefore, we evaluated 16S Sanger sequencing and next-generation sequencing (NGS) to identify bacterial species in the oropharynx of N. atra. Using conventional microbial culture methods and the VITEK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 43 publications
1
15
1
Order By: Relevance
“…In Taiwan, N. atra has the highest infection rate at approximately 80.9% [ 7 ]. Mao et al [ 32 ] identified three important organisms based on comparisons between oral bacteria from N. atra and wound bacterial cultures from envenomed patients, namely M. morganii , P. vulgaris , and Proteus mirabilis. In the current study, these three bacteria were isolated from the oral cavities of venomous snakes, mainly from N. atra and P. mucrosquamatus .…”
Section: Discussionmentioning
confidence: 99%
“…In Taiwan, N. atra has the highest infection rate at approximately 80.9% [ 7 ]. Mao et al [ 32 ] identified three important organisms based on comparisons between oral bacteria from N. atra and wound bacterial cultures from envenomed patients, namely M. morganii , P. vulgaris , and Proteus mirabilis. In the current study, these three bacteria were isolated from the oral cavities of venomous snakes, mainly from N. atra and P. mucrosquamatus .…”
Section: Discussionmentioning
confidence: 99%
“…These pathogens were also identified in the oropharynx of N . atra [ 13 , 65 , 66 ], which suggested that they may come from the snake’s mouth during envenoming. In addition, a few pathogens were identified only in the later surgeries, suggesting secondary colonization or nosocomial infection.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, all patients received antibiotics before obtaining the surgical samples, which might have changed the bacterial loads and complexity. Therefore, we suggest a next-generation sequencing technique to better discriminate wound bacteriology [ 13 ]. Nevertheless, we reported only deep tissue cultures, which generally are accepted as the gold standard to diagnose wound infection and as guidance for further antibiotics administration [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations